SINKRONISASI ANTARA INDIKATOR KINERJA DALAM RPJMD BUKITTINGGI 2016-2021 DAN SUSTAINABLE DEVELOPMENT GOALS - Gina Havieza Elmizan; Suhairi Suhairi; Fauzan Misra (Jurnal Pembangunan Nagari, 2020)
Indonesia agreed and has compiled related rules to be able to align the direction of national development with SDGs, up to the regional level, following UCLG ASPAC directives to localize SDGs. However, the alignment effort is only at the provincial level and still in the planning stage despite the running of SDGs nearly reached its one-third period. This research aims to trace the efforts of the Bukittinggi Government in synchronizing RPJMD for 2016-2021 with SDGs. A qualitative approach with the case study method by Yin (2018) was used in this study, with data collection techniques in the form of documentation comparison between RPJMD and SDGs. It is found that out of 17 goals of the SDGs, the Bukittinggi RPJMD synchronized 76% of SDGs goals or with a total of 38 performance indicators with different distributions to the SDGs goals. The SDGs with the most aligned/synchronous indicators with Bukittinggi RPJMD are in SDGs number 16, and the most out of sync goals are to SDGs number 7, 14, 15, and 17.